1989
DOI: 10.1117/12.962927
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Of The Merits Of Open-Back, Symmetric Sandwich, And Contoured Back Mirrors As Light-Weighted Optics.

Abstract: There is a need for reliable mirrors which are both light-weight and stiff. However very little documentation exists that compare different types of light weight mirrors. This lead to this parametric study to compare different mirror types, namely, contoured back mirrors, symmetric sandwich mirrors, and open back mirrors. This paper examines each mirror type as compared in each of several categories: 1) Self weight induced deflection, which is a product of stiffness and weight, for mirrors mounted on their bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…with E e and ρ e representing the relative density of materials and the modulus of elasticity for the eth cell, respectively; E 0 is the modulus of elasticity for a given material (ρ e = 1); P is the penalty factor; and, in this study, the penalty factor was taken as P = 3 for the study calculation, with ρ and ρ representing the lower and upper limits of cell density, respectively. From Equation (2), ρ e is equal to 1 or 0 indicating that the material of the cell is taken as the selected material or no material, respectively. Therefore, the configuration of the structure can be described by the relative density of the material of each cell.…”
Section: Description Of the Back Ribs Layout And Height-constraint Design Methods Of Space Mirrormentioning
confidence: 99%
See 1 more Smart Citation
“…with E e and ρ e representing the relative density of materials and the modulus of elasticity for the eth cell, respectively; E 0 is the modulus of elasticity for a given material (ρ e = 1); P is the penalty factor; and, in this study, the penalty factor was taken as P = 3 for the study calculation, with ρ and ρ representing the lower and upper limits of cell density, respectively. From Equation (2), ρ e is equal to 1 or 0 indicating that the material of the cell is taken as the selected material or no material, respectively. Therefore, the configuration of the structure can be described by the relative density of the material of each cell.…”
Section: Description Of the Back Ribs Layout And Height-constraint Design Methods Of Space Mirrormentioning
confidence: 99%
“…Talapatra [1] conducted a study on lightweight and high-stiffness mirror structures and proposed that the arch-shaped structure has certain advantages in weight and stiffness compared with the traditional flat-backed structure in the optimal structural design of the mirror. In the study of the mirror design, Valente and Vukobratovich [2] investigated the design of the mirror with different lightweight apertures in terms of the deformation caused by the self-weight of the structure and the manufacturing constraints. Fan et al [3] analyzed the advantages and disadvantages of mirror configurations with various back shapes and lightweight holes in terms of the lightweight rate, structural stiffness, thermal stability, and manufacturing processability, which have a certain guiding significance for the lightweight structure design of mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it must be reduced as much as possible. Daniel Vukobratovich summed up a formula for calculating the quilting amplitude [20]. It can be expressed by Equation (2):…”
Section: Quiltingmentioning
confidence: 99%
“…Daniel Vukobratovich found that the sandwich mirror has the best mirror efficiency in 1989 (Figure 3). The mirror efficiency is defined as the total mirror height divided by the mechanical deflection; a high efficiency is desirable [20]. However, the high-precision welding techniques adopted in the fabricating process of metal sandwich mirrors greatly raises costs and risks.…”
Section: Introductionmentioning
confidence: 99%
“…Valente and Vukobratovich made a comparative study of optical performance according to the shape of a primary mirror's substrate. 1 Cho, Richard, and Vukobratovich proposed design criteria to minimize optical aberrations and to obtain the optimum support points of a lightweight primary mirror under a self-weight loading. 2 Genberg and Cormany used a nonlinear programming method for the optimum design of a lightweight primary mirror.…”
Section: Introductionmentioning
confidence: 99%